2000
DOI: 10.1038/35005118
|View full text |Cite|
|
Sign up to set email alerts
|

Nuclear translocation and transcription regulation by the membrane-associated guanylate kinase CASK/LIN-2

Abstract: Membrane-associated guanylate kinases (MAGUKs) contain multiple protein-binding domains that allow them to assemble specific multiprotein complexes in particular regions of the cell. CASK/LIN-2, a MAGUK required for EGF receptor localization and signalling in Caenorhabditis elegans, contains a calmodulin-dependent protein kinase-like domain followed by PDZ, SH3 and guanylate kinase-like domains. In adult rat brain, CASK is concentrated at neuronal synapses and binds to the cell-surface proteins neurexin and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
309
2
3

Year Published

2000
2000
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(326 citation statements)
references
References 21 publications
12
309
2
3
Order By: Relevance
“…Both proteins could be coimmunoprecipitated from rat brain extracts (48). Although the T-box transcription factor tbr-1 promotes CASK translocation to the nucleus to regulate reelin expression, syndecan has been shown to bind CASK to the plasma membrane and prevent nuclear translocation even in the presence of tbr-1 (42). However, a regulatory mechanism for the differential subcellular targeting of CASK is not known (49).…”
Section: Fig 4 Luciferase Assay To Quantify Sicd Generation In Hek2mentioning
confidence: 99%
See 2 more Smart Citations
“…Both proteins could be coimmunoprecipitated from rat brain extracts (48). Although the T-box transcription factor tbr-1 promotes CASK translocation to the nucleus to regulate reelin expression, syndecan has been shown to bind CASK to the plasma membrane and prevent nuclear translocation even in the presence of tbr-1 (42). However, a regulatory mechanism for the differential subcellular targeting of CASK is not known (49).…”
Section: Fig 4 Luciferase Assay To Quantify Sicd Generation In Hek2mentioning
confidence: 99%
“…Two L27 domains, a PDZ, a SH3, and a Hook domain form the middle part of the molecule. The PDZ domain of CASK is required for syndecan binding, whereas the guanylate kinase domain is required for binding to tbr-1 (42,43). The mechanism by which the subcellular distribution of CASK is regulated remains unknown.…”
Section: Syndecan-processing and Subcellular Distribution Of Cask-mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its role as an organizer of protein complex assembly, it has been shown that CASK interacts via its guanylate kinase-like domain with the T-box transcription factor Tbr-1 (25). In conjunction with Tbr-1 it enters the nucleus and binds to the palindromic T-element (AATTTCACACCTAGGTGTGAAATT), thereby acting as a co-activator of transcription of T-elementcontaining promoters, e.g.…”
mentioning
confidence: 99%
“…It is currently unknown how mLin-7C localizes at the nectin-based cell ± cell junctions, but the present results indicate that mLin-7C is associated with afadin or ZO-1 indirectly through an unknown molecule in an actin cytoskeleton-independent manner. mLin-7C forms a ternary complex with mLin-2 and mLin-10 (Borg et al, 1998;Butz et al, 1998) and each of these molecules interacts with many other molecules: mLin-7 with PSD-95, type 2 NMDA receptors, BGT-1, Pals, b-catenin, and VAM-1 (Jo et al, 1999;Perego et al, 1999Perego et al, , 2000Kamberov et al, 2000;Tseng et al, 2001); mLin-2 with neurexin, syndecan, protein 4.1, calcium channels, Tbr-1, hDlg, JAM, and rabphilin3A (Hata et al, 1996;Cohen et al, 1998;Hsueh et al, 1998Hsueh et al, , 2000Maximov et al, 1999;Nix et al, 2000;Martinez-Estrada et al, 2001;Zhang et al, 2001); and mLin-10 with amyloid precursor protein, Munc-18, neurexins, and KIF17 (Borg et al, 1996;Okamoto and SuÈ dhof, 1997;Biederer and SuÈ dhof, 2000;Setou et al, 2000). These earlier observations together with the present results suggest that these proteins directly or indirectly binding to mLin-7 are recruited to the nectinbased cell ± cell junctions.…”
Section: Discussionmentioning
confidence: 99%